Radioimmunotherapy of Xenografts of Human Pancreatic Carcinomas - Intravenous and Intratumoral Application of 131l-Labelled Monoclonal Antibodies - Klapdor, R.; Lander, S.; Bahlo, M.; Montz, R. (Nuklearmedizin - NuclearMedicine, 1986)
The effects of radioimmunotherapy were tested in xenografts of 2 different human pancreatic carcinomas comparing the intravenous and intratumoral application. On principle, intravenous injections of high doses of 131l-anti- Ca 19-9 or -BW 494/32 may inhibit tumor growth. In view of the low direct radiation dose (360-2100 rad), however, other factors than direct toxic effects have to be discussed, e. g. systemic effects due to the high whole-body irradiation. Intratumoral application, however, may induce tumor regression or growth inhibition due to the high local irradiation dose. Consequently, this treatment modality might be of clinical value at least in some patients.Die Möglichkeit einer Radioimmuntherapie von Xenotransplantaten humaner Pankreaskarzinome wurde an 2 verschiedenen Pankreaskarziomen nach intravenöser und intratumoraler Applikation untersucht. Im Prinzip kann eine intravenöse Injektion von 131J-anti-CA 19-9 oder-BW 494/32 das Tumorwachstum hemmen. Angesichts der nur geringen direkten Strahlendosis (360-2100 rad) müssen jedoch andere Faktoren ursächlich diskutiert werden, z.B. unspezifische Effekte infolge der hohen Gesamtkörperbestrahlung. Nach intratumoraler Applikation scheint eine Hemmung des Tumorwachstums bzw. eine Tumorregression dagegen über einen lo- möglich. Die intratumorale Therapiemodalität könnte zumindest für einzelne Patienten von klinischer Bedeutung sein.